Ankle fracture with syndesmotic injury treated by screw fixation: a prospective study on clinical and radiographic outcomes - Li, Xiaodong; Liu, Pengcheng; Duan, Ran; Wang, Xiang; Zhu, Qianhua; Ni, Shuangling; Wang, Xiaoqing (Frontiers in Surgery, 2025)
PurposeThe syndesmotic screws are frequently utilized in the treatment of unstable ankle fractures. However, significant controversies persist regarding their optimal application strategies. This study aims to investigate the dynamic changes in syndesmotic reduction among patients with unstable ankle fractures following syndesmotic screw fixation and to explore the relationship between malreduction and functional outcomes.MethodsPatients with unstable ankle fractures who underwent open reduction and internal fixation (ORIF) with syndesmotic screw fixation from January 2020 were prospectively enrolled. Syndesmotic screws were routinely removed 8–12 weeks post-fixation. All patients were followed up at five time points: immediately after internal fixation, prior to syndesmotic screw removal (8–12 weeks), and at 3, 6, and 12 months post-initial fixation. Evaluations included imaging (Computed Tomography, CT), functional outcomes [Ankle and Hindfoot Function Scoring System (AOFAS), Olerud-Molander Ankle Score (OMAS)], and pain assessment (Visual Analog Scale, VAS).ResultsFrom January 2020 to January 2021, a total of 26 patients were included in this study. The incidence of malreduction at the five follow-up time points was 69.2% (18/26), 61.5% (17/26), 50% (13/26), 61.5% (16/26), and 61.5% (16/26), respectively. Malreduction of the anterior tibiofibular distance and fibular rotation were the primary contributing factors. Functional outcomes were significantly worse for patients with malreduction following syndesmotic screw removal compared to those without malreduction (p < 0.05).Conclusions(1) Dynamic changes in syndesmotic reduction were observed at various time points within one year post-surgery. Removal of the syndesmotic screw improved syndesmotic reduction to some extent; however, re-diastasis may occur after weight-bearing. (2) Syndesmotic malreduction following screw removal was associated with poorer ankle functional outcomes.